2013
DOI: 10.5296/ijld.v3i3.3673
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organizational Culture On Lecturers’ Job Satisfaction and Performance (A Research in Muhammadiyah University throughout East Java)

Abstract: This study aimed to clarify the effect of organizational culture on job satisfaction and its impact on lecturers' performance. The population of the study is the lecturers of the Muhammadiyah University throughout East Java namely 1881 people, with random sampling it was obtained a sample of 200 people. For collecting data, questionnaires and interviews were used. Data analysis techniques applied SEM (Structural Equation Modeling) with the use of AMOS software. The results showed that: (1) Organizational cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
1
11
0
7
Order By: Relevance
“…Fanggidae et al 2016found a positive and significant influence between the work environment culture which was proxied by spirituality and organizational commitment and job satisfaction of lecturers. Sangadji and Sopiah (2013) also found that organizational culture positively and significantly influenced job satisfaction of lecturers.…”
Section: Introductionmentioning
confidence: 82%
“…Fanggidae et al 2016found a positive and significant influence between the work environment culture which was proxied by spirituality and organizational commitment and job satisfaction of lecturers. Sangadji and Sopiah (2013) also found that organizational culture positively and significantly influenced job satisfaction of lecturers.…”
Section: Introductionmentioning
confidence: 82%
“…Sales are part of the promotion, and promotion is part of the overall marketing strategy system [23]. Consumer satisfaction can create a reasonable basis for repeat purchases and build consumer loyalty from word-ofmouth recommendations that can benefit the company [24]. Competitiveness is a marketing strategy notion related to a company's capacity to create value in competition with other companies.…”
Section: Marketing Strategy Indicatormentioning
confidence: 99%
“…Personal Selling according to Sunyoto (2015) is the presentation of products to consumers by a representative company salesperson. According to Sangadji and Sopiah (2013) personal selling is a conversation with one or more prospective buyers or what is commonly referred to as an oral presentation at creating sales. Based on the above definition, it can be concluded that personal selling is a form of company communication to consumers through face-to-face to introduce the products offered in the hope that consumers know and buy these products.…”
Section: Personal Sellingmentioning
confidence: 99%